Pengaruh Inflasi terhadap Pertumbuhan Aset dengan Struktur Modal sebagai Variabel Intervening - Nadia Rizki Rahmalia; Ruhadi Ruhadi; Ine Mayasari (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
This study aimed to determine the direct effect and indirect effect of inflation on asset growth of Islamic Commercial Banks in Indonesia through capital structure as intervening variable. This research uses secondary data sourced from Bank Indonesia websites and annual report published by 11 Islamic Commercial Banks in Indonesia on 2013-2019. Using a purposive sampling technique. The method that used in this reseach is descriptive-associative through quantitative approach using path analysis (SEM-PLS). The result of this research showed that directly inflation has positive and significant effect to assets growth of Islamic Commercial Banks in Indonesia. Meanwhile, directly inflation has no significant effect to capital structure (Debt to Asset Ratio). Directly, capital structure (DAR) has no significant effect to assets growth of Islamic Commercial Banks in Indonesia. And indirectly, inflation has no significant effect to assets growth of Islamic Commercial Banks through capital structure (DAR) as intervening variable or mediator.